The wars of the Iroquois a study in intertribal trade relations - Hunt, George T. (Univ. of Wisconsin Press, 1940)
Traces intertribal trade relations of the Iroquois and the impact Europeans had on this in the seventeenth century.
Literaturverz. S. 185 - 200
Keywords: Geschichte 1609-1653; Indianer; Indians of North America - Commerce; Indiens - Amérique du Nord; Iroquois (Indiens) - Guerres; Indians of North America -- Commerce; Iroquois Indians -- Wars; Geschichte; Krieg; Irokesen